The emergent literacy development of pre-schoolers and their home supports for literacy - Willenberg, Ingrid Anthea (Division of Communication Sciences and Disorders, 2017)
The aim of the study was to assess the emergent literacy knowledge of a group of South African pre-schoolers from low and low-middle class families and to explore their home supports for literacy. The sample comprised 24 subjects, aged between 5 years 9 months and 6 years 5 months. Sixteen of the subjects were from low-middle class families, while the remaining eight were from low-class families. The emergent literacy knowledge of the children was assessed using the Emergent Literacy Assessment Profile (ELAP), which was developed for the purpose of this study. The profile included subtests derived and modified from existing batteries developed elsewhere in the world for assessment of emergent literacy. The children's home supports for literacy were ascertained by means of personal interviews conducted with the parents in their home environments. Although both groups exhibited poor emergent literacy knowledge in general, it was found that there were statistically significant differences in the performance of the two groups on several subtests of the ELAP. The group of children from low-middle class families displayed relatively better literacy knowledge than their counterparts from low-class families. This group (i.e. the low-middle class group) also had better access to home supports for literacy. Thus, differences in home supports for literacy were strongly linked to differences in socio-economic status. The findings of the study confirm the much documented finding that home environments impact greatly on children's emergent literacy development. The finding that even the children with relatively more favourable home environments displayed deficits in emergent literacy knowledge indicates the urgent need to promote the emergent literacy development of pre-schoolers in South Africa, particularly those from historically disadvantaged communities. This has implications for parents, teachers, educare workers, librarians and speech-language therapists, inter alia.